2019
DOI: 10.1021/acsenergylett.8b02499
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Layered Ni-Rich NCMA Cathode for Lithium-Ion Batteries

Abstract: O 2 (NCM) cathodes have been the archetypes of current high-energy-density cathodes for Li-ion batteries. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
174
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(179 citation statements)
references
References 31 publications
4
174
1
Order By: Relevance
“…Several studies have shown the C lattice parameter to contract upon the H2-H3 transition and this is assumed to be responsible for the grain boundary cracking. [9,10,11] We believe that the same mechanism is responsible for cleavage observed in micron sized NMCA single crystals. Figure 4(d) shows a HAADF STEM micrograph of a fractured NMCA particle with a C element map and EELS element maps comparing Ni and Li, as well as Ni and O distributions.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Several studies have shown the C lattice parameter to contract upon the H2-H3 transition and this is assumed to be responsible for the grain boundary cracking. [9,10,11] We believe that the same mechanism is responsible for cleavage observed in micron sized NMCA single crystals. Figure 4(d) shows a HAADF STEM micrograph of a fractured NMCA particle with a C element map and EELS element maps comparing Ni and Li, as well as Ni and O distributions.…”
Section: Resultsmentioning
confidence: 71%
“…The secondary particles consisted of large grains in the range of 1-2 µm and showed the typical grain boundary fracturing as described in literature. [9] However, the NMCA grains were much bigger than the primary particles of NMC811 (figure (2)) and hence less new surface is generated upon grain boundary fracture. The single crystals however showed a different failure mode: Many of them exhibited intraparticle fractures.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result, a straightforward Al/Mn codoping approach is developed for the Ni‐rich cathodes to incorporate their individual advantages. To verify this viewpoint, Sun and co‐workers synthesize a quaternary system of LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O 2 , which can deliver a high capacity of 228 mAh g −1 , and obviously outperforms the benchmarking cathodes (only containing Al or Mn) in long‐term cycling stability . More significantly, it has been proved as an efficient avenue just doping a small amount of Al for Ni in the crystal lattice to strikingly enhance the chemical stability against moisture air through restraining the formation of residual lithium on the surface region as compared to the other Al‐absent Ni‐rich cathodes ( Figure a) .…”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
“…Nickel-Cobalt-Aluminum (NCA) is characterized by high reversible capacity, long cycle life and a high operating potential (3.6 V vs. Li + /Li), which are desired properties of cathode materials for lithiumion batteries. 9 At present, NCA cathode materials are fabricated by one of two main synthetic routes. In one route, the NCA precursor is synthesized by a co-precipitation method, and the NCA cathode material is then obtained by high-temperature lithiation of the precursor.…”
Section: Introductionmentioning
confidence: 99%